Hydrogen-bonding interactions in crown-(thio)urea complexes with anions, chemical warfare agents and simulants. Issue 11 (2nd November 2019) - Cave, Hannah; Ede, Jayne A.; Sambrook, Mark R.; Dodd, Howard; Fucassi, Flavia; Cragg, Alexander S.; Lansley, Adam H.; Cragg, Peter J.
ABSTRACT: Benzocrown ethers incorporating phenyl and nitrophenyl urea and thiourea moieties were synthesised. Both the nitrophenyl urea and thiourea derivative gave a fluoride-specific colorimetric response but only the urea derivative bound the organophosphonate nerve agent simulants dimethyl methylphosphonate (DMMP) and diisopropyl methylphosphonate (DIMP). This suggested an application as sensors for the nerve agents sarin, soman and cyclosarin which release fluoride upon hydrolysis. Although no fluoride-induced response was observed in the UV-visible spectrum, binding to soman was determined by 1 H NMR. DFT computational simulations suggested that the two crowns adopt different conformations in which both can bind fluoride but only the urea derivative can bind DMMP, DIMP and soman. The results show that, for this system, simulant- and soman-binding behaviours are in good agreement. Graphical Abstract: